Addressing urban shrinkage in small and medium sized towns : shrink smart and re-grow smaller - Schlappa, Hans; Nishino Tatsuya (Emerald Publishing Limited, 2021)
In Europe and other developed countries, much of the population live in small and medium sized towns. For many such places the pursuit of growth is no longer a viable strategic option. As the ability of small towns to compete with larger cities for private investment and government support diminishes, the number trapped in a spiral of long-term decline grows. Beginning with a brief overview of the global context, highlighting that urban shrinkage and decline is a widespread problem, Schlappa and Nishino illustrate how small towns can generate sustainable forward strategies in contrasting institutional contexts by fostering co-production, adjusting public facilities and right sizing the urban area. The analytical tools and practical examples provided by Schlappa and Nishino are relevant for political and administrative decisionmakers, leaders of civil society and business organisations in developing locally appropriate, creative and robust strategies to shrink smart and re-grow smaller.
Includes index.
Keywords: City planning.; Urban policy.; Shrinking cities.; Political Science -- Public Policy / City Planning & Urban Development.; Urban & municipal planning.; elektronické knihy; electronic books